A Classroom Application of Concept-Based Language Instruction (C-BLI). (20th July 2022) - Benhamlaoui, Maroua; Gánem-Gutiérrez, Gabriela Adela
Abstract : This study reports on an investigation of the potential of Concept Based Language Instruction (C-BLI) for enhancing EFL learners' understanding of the concept of tense/aspect in English and their use of associated forms; past simple, past continuous, and present perfect. C-BLI was compared to a grammar presentation approach based on the Presentation-Practice-Production (PPP) model. Participants included 45 adult learners of L2 English from an Algerian University. Drawing on a pre-, post-, delayed post-test research design the study revealed the effectiveness of C-BLI over PPP for improving the participants' understanding of the concept of tense/aspect as well as their use of the three target forms.